An efficient synthesis of tetraazapentacenes - Tverskoy, Olena; Rominger, Frank; Peters, Anastasia; Himmel, Hans-Jörg; Bunz, Uwe H. F. (Angewandte Chemie. International edition, 2011)
Organic electronics on demand? The palladium-catalyzed coupling of aromatic ortho-diamines with substituted dichloroquinoxalines furnishes N,N-dihydrotetraazaacenes, which were oxidized by MnO2 into the corresponding tetraazapentacenes (see structures; N blue, Cl green, Si yellow). The modular synthesis of these acenes allows the introduction of any substituent by choice of the proper quinoxaline derivative.